2022
DOI: 10.3389/fimmu.2022.797312
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Mitigates Sepsis-Related Neuroinflammation via Modulating Gut Microbiota and Metabolites

Abstract: Gut microbiota affects the functions of brains. However, its mechanism in sepsis remains unclear. This study evaluated the effect of metformin on ameliorating sepsis-related neurodamage by regulating gut microbiota and metabolites in septic rats. Cecal ligation and puncture (CLP) was used to establish the sepsis-related neurodamage animal models. Metformin therapy by gavage at 1 h after CLP administration was followed by fecal microbiota transplantation (FMT) to ensure the efficacy and safety of metformin on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…Recently, growing evidence has highlighted the cross-talk between the gut microbiota and sepsis [38]. There was convincing evidence indicating the potential of constituting effective and safe therapies for sepsis by targeting the intestinal microbiota [39,40]. However, the detailed roles of the intestinal microbiota during sepsis remain largely unknown, and effective therapeutic strategies for its clinical application are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence has highlighted the cross-talk between the gut microbiota and sepsis [38]. There was convincing evidence indicating the potential of constituting effective and safe therapies for sepsis by targeting the intestinal microbiota [39,40]. However, the detailed roles of the intestinal microbiota during sepsis remain largely unknown, and effective therapeutic strategies for its clinical application are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, SFH could modulate the abundance of Escherichia_Shigella , Escherichia_coli , Blautia , and other bacteria, restoring them to levels similar to those of healthy mice. As Escherichia_Shigella has the ability to invade and destruct human colonic epithelium ( Belotserkovsky and Sansonetti, 2018 ), it may incur sepsis-related neural inflammation ( Zhao et al, 2022 ). Blautia , an anaerobic bacteria with probiotic traits, plays specific roles in metabolic diseases, inflammatory settings, and bio-transformation ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study reported the negative relevance of Muribaculaceae to IL-6 in the CLP rat brain ( 29 ). In this study, Muribaculaceae was increased in the CLP + BBR group compared to the CLP group.…”
Section: Discussionmentioning
confidence: 99%
“…The processed samples were injected into the analytical equipment. The nontargeted metabolomics approach had been previously described by Zhao et al ( 29 ). The metabolomics analysis performed by the Gas Chromatography-Time-of-Flight Mass Spectrometry (GC-TOF/MS) platform (Gerstel, Germany) integrated processing samples and issuing reports.…”
Section: Methodsmentioning
confidence: 99%